The gene expression signature associated with TP53 mutation/deletion in chronic lymphocytic leukaemia is dominated by the under-expression of TP53 and other genes on chromosome 17p - Lin, Ke; Lane, Brian; Carter, Anthony; Johnson, Gillian G.; Onwuazor, Obiageli; Oates, Melanie; Zenz, Thorsten; Stilgenbauer, Stephan; Atherton, Mark; Douglas, Angela; Ebrahimi, Bahram; Sherrington, Paul D.; et al. (British journal of haematology, 2013)
In chronic lymphocytic leukaemia (CLL), TP53 mutation and deletion are strongly associated with one another and with adverse clinical outcome. Mutant TP53 protein typically accumulates to high levels and has been reported to have transcriptional regulatory activity distinct from that of wild-type TP53. To investigate whether such an effect is relevant to CLL, carefully balanced primary CLL samples with or without TP53 mutation/deletion were compared for their gene expression profiles using high-density DNA microarrays. Ninety-six and eight differentially expressed genes were identified, respectively, using two alternative statistical approaches with different stringencies. None of the differentially expressed genes were known to be regulated by mutant TP53, and only four of the 67 under-expressed genes were known transcriptional targets of wild-type TP53. Significantly, both approaches showed that gene under-expression was the dominant feature of TP53-mutant CLL samples. Furthermore, a disproportionate number of the under-expressed genes were located on chromosome 17p, the most significant being TP53 itself. Together, these results indicate that any transcriptional regulatory effects of mutant TP53 in CLL cells are overshadowed by the under-expression of co-deleted TP53 and other genes on chromosome 17p. Our findings have implications for emerging therapeutic strategies that target mutant TP53.